Teori Hukum Islam Kontemporer dan Pendekatan Sistem dalam Implementasi Ekonomi Keuangan Syariah - Khaerunnisa, Baiq Rodia; Muhajirin, Muhajirin (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
In practice, there are 2 (two) factors that influence the implementation of muamalah or business transactions, namely: whether to gain profit or loss. Conversely, if the risk is an attempt to gain profit on one side, while the other party is harmed, then this violates Islamic law and results in Gharar. Economic exploitation in the form of usury or interest on money and transactions whose clarity is still unknown or called Gharar, is absolutely prohibited by Islamic law. First, it covers aspects of worship, such as laws that regulate human relations with al-Khaliq; second, it covers laws related to the family (al ahwal a sy-syahsyiyah), such as marriage, divorce, reconciliation, wills, inheritance, and hadhanah; third, it covers aspects of muamalah (civil law), namely laws related to relations between humans, such as sales transactions, pawning, grants, debts, loans, mudharabah, joint ventures, luqathah, and so on, which are intended to maintain harmony and order; and fourth, covering economic aspects, such as issues related to the development of wealth and its utilization, such as zakat law, baitul maal, ghanimah assets, and fa'i; taxes, and things that are forbidden, such as usury, hoarding wealth, and consuming the wealth of orphans.